Seleksi Genotipe Jagung Hibrida Toleran N Rendah - nFN Syafrudin; Muhammad Azrai; nFN Suwarti (Buletin Plasma Nutfah, 2013)
Maize Hybrid Genotypes Selection for Low N Tolerance. Syafruddin, Muhammad Azrai, and Suwarti. Most of the maize crop land development in Indonesia are defficient of N, to overcome these obstacles is generally done with N fertilizer. N fertilization beside increasing the cost of production is also causing environmental pollution. Therefore, fertilizer efficiency is required. One effort to reduce N fertilizer usage is the use of low N-tolerant genotypes. Selection of low Ntolerant maize hybrids are expected to found a low N genotypes with high productivity. The experiment was conducted in low land in May-August 2012 in the Bontobili Research Station, Gowa, South Sulawesi. A total of 32 genotypes including check entries were 4 known hybrid Bima- 2, Bima-3, Bima-4, and Bisi-2 were screened in normal rate of N application (200 kg N/ha) and low N (100 kg N/ha). The treatment used experimental randomized complete block design at each fertilization with three replications. To Determine of genotype x N interaction was used combine analysis. The result showed that in selection of tolerance genotypes for low N, beside yield as selection parameter we can also consider leaf chlorophyll, harvest index, number of kernel in ear and seed weight. Genotypes 1044-0 x 1027-11 and AMB07 x CML 161 were tolerance to low N and B11 x 11 is moderat to low N. Three of genotypes have yield equal to 4 check varieties (Bima-2, Bima-3, Bima-4, and Bisi-2). AbstrakSebagian besar lahan pengembangan tanaman jagung di Indonesia defisien N. Untuk mengatasi kendala tersebut umumnya dilakukan dengan pemupukan N. Pemupukan N di samping meningkatkan biaya produksi juga menyebabkan pencemaran lingkungan. Salah satu upaya untuk menekan penggunaan pupuk N adalah penggunaan genotipe yang toleran N rendah. Seleksi genotipe jagung hibrida diharapkan memperoleh genotipe toleran N rendah dengan produktivitas tetap tinggi. Penelitian dilaksanakan di lahan sawah pada Mei- Agustus 2012 di KP Bontobili, Gowa, Sulawesi Selatan. Sebanyak 32 genotipe termasuk empat pembanding Bima-2, Bima-3, Bima-4, dan Bisi-2 diuji pada takaran pupuk N normal (200 kg N/ha) dan N rendah (100 kg N/ha). Penelitian menggunakan rancangan kelompok pada masing-masing pemupukan dengan tiga ulangan. Untuk mengetahui interaksi antara genotipe dengan N dilakukan analisis gabungan. Hasil penelitian menunjukkan bahwa untuk mendapatkan genotipe jagung toleran N rendah yang akurat di samping mempertimbangkan hasil biji, juga mempertimbangkan komponen lainnya, seperti klorofil daun, indeks panen, jumlah biji per tongkol, dan bobot biji. Genotipe 1044-9 x 1027-11 dan AMB07 x CML161 toleran N rendah dan B11 x 11 moderat terhadap N rendah, ketiga genotipe tersebut mempunyai hasil biji setara dengan varietas pembanding Bima-2, Bima-3, Bima- 4, dan Bisi-2.